Predicting the risk of postoperative venous thromboembolism in rhinoplasty patients: a cohort study - Jie Chen; Jianfei Zhang; Xia Xiao; Yujun Tang; Hejin Huang; Wenwen Xi; Lina Liu; Zhengzhou Shen; Jianhua Tan; Feng Yang (Thrombosis Journal)
Abstract Background Venous thromboembolism (VTE) is a rare complication following rhinoplasty surgery, with an occurrence rate generally estimated to be between 0.5% and 1%. In contrast, the occurrence rate of VTE in orthopedic surgeries, particularly in lower limb fracture surgeries, can reach as high as 10% or more. This significant difference highlights the varying risks associated with different surgical procedures and underscores the importance of identifying risk factors specific to rhinoplasty. Despite its relatively low incidence, the potential for VTE in rhinoplasty patients necessitates a thorough analysis of risk factors to enhance patient safety and guide clinical practice. This study aims to analyze the risk factors for postoperative VTE in rhinoplasty patients and develop a predictive model to assist clinicians in identifying at-risk individuals. Methods A retrospective analysis was conducted on the clinical data of 1100 rhinoplasty patients admitted to a cosmetic hospital from January 2016 to January 2022. Patients were divided into Non-VTE group (1012 cases) and VTE group (88 cases) based on the occurrence of VTE within one month postoperatively. General patient information was collected and subjected to univariate analysis. Multivariate logistic regression analysis was used to identify risk factors for postoperative VTE in rhinoplasty patients and establish a predictive model. Internal validation was performed using bootstrapping technique to assess the accuracy and predictive performance of the model. Results Univariate analysis showed that the proportions of IBD, Myocardial infarction, Previous VTE, PICC/central line, Rib graft, and History of nasal surgery were significantly higher in the VTE group compared to the Non-VTE group (all P < 0.05). Multivariate logistic regression analysis identified IBD, Myocardial infarction, Previous VTE, Rib graft, and History of nasal surgery as independent risk factors for VTE (P < 0.05). The constructed predictive nomogram model demonstrated good calibration and predictive accuracy, with an area under the ROC curve of 0.845, indicating excellent discrimination and clinical predictive performance. Conclusion IBD, Myocardial infarction, Previous VTE, Rib graft, and History of nasal surgery are independent risk factors for postoperative VTE in rhinoplasty patients. The predictive model effectively assesses the risk of VTE in patients, providing important guidance for clinical decision-making.